In situ monitoring hydrogen isotope retention in ITER first wall. (19th February 2016) - Mukhin, E.E.; Andrew, P.; Anthoine, A.D.; Bazhenov, A.N.; Barnsley, R.; Bukreev, I.M.; Bukhovets, V.L.; Chernakov, A.P.; Gorodetsky, A.E.; Kochergin, M.M.; Koval, A.N.; Kukushkin, A.B.; et al.
Abstract: Tritium retention inside the vacuum vessel is a potentially serious constraint in the operation of large-scale fusion machines like ITER. An in situ diagnostics for first wall H/D/T retention by laser induced desorption spectroscopy (LIDS) is proposed for use between plasma discharges. The technique is based on local baking of the first wall by laser irradiation and subsequent analysis of the in-vessel gas by optical emission spectroscopy of plasma radiation. The local heating implementation, kinetics of H/D/T thermal extraction and the accuracy of optical emission spectroscopy measurements are analysed. To resolve the H/D/T lines spectroscopically, their thermal broadening should be minimized to prevent overlapping of the line shapes. A comparative performance analysis of several types of plasma sources with relatively cold ions is made including the following types of discharges: Penning, RF multipactor, laser torch and ECR. All these radiation sources require rather low power and could be used for remote in situ measurements of relative densities of the thermally extracted hydrogen isotopes.